Vida é milonga: troca e dádiva no ritual-tango - Silva, Cristiana Felippe e (2016)
This ethnographic research analyzes the tango party as an urban ritual of exchange and liminality, taking into account urban and body anthropology transversed by a gender perspective. The goal is to recover the milongueras and other hidden narrators from the official history, by reflecting on how the dance reframes roles assigned for the representation of gender, ethnicity, and intergenerationality. The documentary, bibliographic and field research with observant participation starts from tango parties in São Paulo and extends to the circuits and paths of tango dancers along the River Plate region of Buenos Aires (Argentina) and Montevideo (Uruguay), where this rhythm originated. The study investigates in formal interviews and casual conversations into the embodiment of this ballroom dance party with their specific codes and gestures, as social organizers and their relations of dominion and power. Through striking elements of tango, as the glance, the walking and the embrace, that ballroom dance party is analyzed as the search for experience of reciprocity, meaning and sociability, whose agents are protagonists of exchanges and encounters, capable of transforming the city uses; thus, recreating the urban spaces and themselves